Nutrient Incorporation in First Feeding Seahorses Evidenced by Stable Carbon Isotopes - Sonia Valladares; Miquel Planas (Animals, 2021)
Nutritional issues are among the most critical factors in the initial survival of juvenile seahorses. Currently, there is a knowledge gap on the relationship between nutrient assimilation and the effects on initial mortalities and growth. In the present study, the stable isotope approach was used to assess the incorporation of two live preys (Artemia and copepods) in juvenile seahorses Hippocampus guttulatus. The changes in stable carbon isotope (δ13C) values were studied through two feeding experiments: feeding on Artemia or copepods (experiment 1), and shifting feeding from copepods to Artemia (experiment 2). In experiment 1, after 24–48 h of feeding, juvenile seahorses exhibited small but progressive changes in δ13C values towards those of the corresponding diet, indicating that the assimilation of the food offered was progressively enhanced from days 2–3. Similarly, in experiment 2, a diet shifting from copepods to Artemia caused an increase in δ13C values, reflecting a switch towards the isotopically enriched new diet (Artemia metanauplii). Differences in the assimilation efficiency of preys offered are discussed based on growth and survival rates. The enhanced growth performances and survivals achieved when the juveniles were fed on copepods could be related to higher efficient assimilation of copepods compared to Artemia. The present study demonstrates that the consumption and further assimilation of preys by juvenile seahorses could be traced using stable carbon isotopes. The research on nutrient assimilation of juvenile seahorses should enhance our knowledge on nutrient processes in developing seahorses for a better understanding of initial ontogeny in the early life stages of the species.